Experimental Study on Pump-driven Two-phase Cooling Loop for High Heat Flux Avionics - Wang Jiaxuan; Song Xia; Gao Tianyuan; Shi Junye; Chen Jiangping (Zhileng xuebao)
Aviation applications are facing the challenges of cooling high-power and high-heat-flux electronic equipment. Traditional cooling methods cannot cope with thermal requirements greater than a heat flux of 100 W/cm2. In this study, the ground test bench of a pump-driven two-phase cooling loop (MPCL) system is constructed, and the control strategy of the system is designed. The cooling ability and resistance characteristics of the system are tested, and the mathematical model is developed. The results show that the mechanical pump drives the two-phase cooling system with good thermal performance. The designed copper cold plate is able to effectively handle 6 kW concentrated heat sources with a heat flux of 120 W/cm2. A 10 kW heat source can be effectively cooled by the MPCL system using 70% less working fluid than single-phase cooling under designed working conditions. The surface temperature of the heating element can be stabilized at 63–70 °C, which meets the temperature requirements of the chip. Additionally, the temperature is uniform between the evaporator branches, with a temperature difference below 5 ℃. The pressure drop of the phase-change segment is below 400 kPa, and the resistance characteristics can be described by the Kim and Mudawar models.